PENGARUH KUALITAS PELAYANAN KESEHATAN DAN FASILITAS RUMAH SAKIT TERHADAP KEPUASAN PASIEN RAWAT JALAN DI RUMAH SAKIT KIA PKU MUHAMMADIYAH KOTAGEDE YOGYAKARTA - Ary Subiyantoro; Prihartanto Eko W; Purwanta Purwanta; Nabilah Bilqis (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
This study aims to determine how much influence the quality of health services and hospital facilities have on outpatient satisfaction at the PKU Muhammadiyah Kotagede KIA Hospital, Yogyakarta, partially or simultaneously. The method used in this study is a quantitative method, where data collection uses a questionnaire. The sample in this study amounted to 30 employees, where these employees served at KIA PKU Muhammadiyah Hospital Kotagede Yogyakarta. Validity test which shows that the statement in this study is valid, while the reliability test using Cronbach Alpha is declared reliable. This study uses multiple linear regression analysis. The results of this analysis indicate that: (1) Health Service Quality has a positive effect on outpatient satisfaction of 0.318. (2) Hospital facilities have a positive effect on outpatient satisfaction of 0.334.